Steviol Glycosides Supplementation Affects Lipid Metabolism in High-Fat Fed STZ-Induced Diabetic Rats - Kurek, Jakub Michał (Nutrients, 2020)
A number of health-promoting properties of Stevia rebaudiana Bertoni and its glycosides, including the antihyperglycemic activity, have been found. The mechanisms of the antidiabetic action of stevia have not been fully understood. The aim of this study was to evaluate the effects of supplementary steviol glycosides on high-fat fed streptozotocin-induced diabetic rats with particular attention to lipid metabolism. The experiment was conducted on 70 male Wistar rats, of which 60 were fed a high-fat diet for 8 weeks followed by intraperitoneal injection of streptozotocin, to induce type 2 diabetes. Afterwards, rats were divided into six groups and fed a high-fat diet supplemented with pure stevioside or rebaudioside A, at two levels (500 or 2500 mg/kg body weight (b.w.)) for 5 weeks. Three additional groups: diabetic untreated, diabetic treated with metformin, and healthy, served as respective controls. Blood and dissected internal organs were collected for hematological, biochemical, and histopathological tests. It was found that dietary supplementation with steviol glycosides did not affect blood glucose, insulin, and insulin resistance indices, antioxidant biomarkers, but normalized hyperlipidemia and affected the appetite, as well as attenuated blood liver and kidney function indices, and reduced tissular damage in diabetic rats. Steviol glycosides normalize lipid metabolism and attenuate internal organs damage in diabetes.